2019
DOI: 10.1039/c9ra00781d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel scaffold with substrate elasticity mimicking physiological-niche promotes proliferation of functional keratinocytes

Abstract: High numbers of autologous human primary keratinocytes (HPKs) are required for patients with burns, wounds and for gene therapy of skin disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In our earlier work, we have demonstrated that soft substrate can delay the onset of replicative senescence in BM-hMSCs [7], which was later supported by observations from other groups as well [16]. We demonstrated the same with patient derived keratinocytes as well [8].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our earlier work, we have demonstrated that soft substrate can delay the onset of replicative senescence in BM-hMSCs [7], which was later supported by observations from other groups as well [16]. We demonstrated the same with patient derived keratinocytes as well [8].…”
Section: Discussionsupporting
confidence: 83%
“…However, out of the four ECMs tested, gelatin showed the best result in terms of PD/passage and final CPD before growth arrest. While cells on TCP had 2 8 times increase in total cell number, cells on gelatin coated plastic had 2 14 times increase in number before they reached growth arrest. However, it should be noted that the cells entered growth arrest at the same time irrespective of coating indicating no effect of the ECM on the culture duration at which growth arrest happens.…”
Section: Ecm Protein Coating Enhances the Proliferation Rate Of Mesenchymal Stem Cells In Vitromentioning
confidence: 97%
See 1 more Smart Citation
“…The migration activity of the cell was influenced by the presence of integrin and matrix metalloproteinases expression. Besides, a study on the polyacrylamide gel coated with collagen I indicate the KCs respond to IFN Ƴ responsive genes (HLA DR and CXCL10) [ 132 ]. The presence of these genes promoted the excellent expansion of KCs for wound healing.…”
Section: In Vivo and In Vitro Studiesmentioning
confidence: 99%
“…Healthy skin specimens were collected from plastic surgery department of B.Y.L. Nair Charitable Hospital, Mumbai, upon approval of the Institute Ethics Committee (IEC) of IIT described earlier after obtaining the written, informed consent (Das et al, 2019, Mogha et al, 2019, Purwar et al, 2006 .…”
Section: Human Primary Keratinocyte Isolation and Culturementioning
confidence: 99%